Compatibilization of recycled polypropylene and recycled poly (ethylene terephthalate) blends with SEBS-g-MA - Luciana Maria Guadagnini Araujo; Ana Rita Morales (Polímeros, 2018)
Abstract The compatibilization of recycled PP/PET blend with high and low concentration (20 and 5 phr) of elastomer functionalized by maleic anhydride (SEBS-g-MA) was achieved. Recycled polypropylene from plastic industry and recycled PET from post-consumer bottles was used. PP/PET blends: 80:20 w/w, 50:50 w/w and 20:80 w/w were prepared in an internal mixer for mechanical properties, thermal properties, morphology and rheological properties. SEBS-g-MA promoted compatibilization of the PP/PET blends and improved their properties. With an increasing compatibilization level, the refinement of morphology was observed in the PET rich blend. Compatibilized blends showed negative deviation in the PET glass transition temperature related to neat PET, demonstrating that compatibilization was very successful. PET crystallization was accelerated in the blends due to PP presence that enhanced nucleation. It was found that the 50/50/20 blend showed huge potential for textile fiber application and that of 80/20/20 showed more intermediary properties than neat polymers.